2018
DOI: 10.1002/ppsc.201700416
|View full text |Cite
|
Sign up to set email alerts
|

Energy Back Transfer Induced Color Controllable Upconversion Emissions in La2MoO6:Er3+/Yb3+ Nanocrystals for Versatile Applications

Abstract: Color controllable Er3+/Yb3+‐codoped La2MoO6 upconverting nanocrystals are successfully synthesized via a facile sol‐gel method. Under the irradiation of 980 nm light, the entire samples exhibit dazzling upconversion (UC) emissions arising from the intra‐4f transitions of Er3+ ions and the UC emission intensity is strongly dependent on the Yb3+ ion concentration. Moreover, by controlling the Yb3+ ion concentration, the emission color is changed from green to yellow and finally to red as a result of the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…By evaluating the refinement parameters ( R wp , R p and χ 2 ), it can be suggested that the results are reliable. LMO:0.2Eu 3+ , 0.6Bi 3+ phosphors belong to I/42m(121) space group 25 . The unit crystal structure of the LMO host lattice is modeled using the Diamond software.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By evaluating the refinement parameters ( R wp , R p and χ 2 ), it can be suggested that the results are reliable. LMO:0.2Eu 3+ , 0.6Bi 3+ phosphors belong to I/42m(121) space group 25 . The unit crystal structure of the LMO host lattice is modeled using the Diamond software.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in summary, La 3+ ions should be replaced by Bi 3+ ions or Eu 3+ ions. Meanwhile, the percentage differences among the dopants and substituted ion are calculated 25 as follows.Dr=RsRdRs×100%where Dr is the radius percentage difference. Rs and Rd denote the ionic radii of substituted ions and dopants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated above, the 5 D 1 level can be populated from the 5 D 0 level by means of thermal excitation, leading to the population redistribution between the 5 D 1 and 5 D 0 levels at high temperature. To further comprehend the temperature-induced population redistribution phenomenon, the temperature-induced population redistribution ability (PRA) was evaluated utilizing the following expression: 37,38 In this formula, I U , I L , A , Δ E , k , and T have the same meaning as described in eqn (1) . Based on the fitting results, the PRA value was calculated, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%